2013
DOI: 10.1111/imb.12019
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of 30K proteins during silk gland degeneration by a caspase‐dependent pathway in Bombyx

Abstract: The 30K proteins are involved with important functions in the growth and development of Bombyx mori. In this study, the synthesis and regulation of 30K proteins were examined during the degeneration of Bombyx silk glands. On day 3 of the fifth instar, the protein level of 30Kc19 was low, whereas the silk proteins were rapidly synthesized. However, synthesis and accumulation of the 30Kc19 protein significantly increased at the prepupal stage and on day 1 of the pupal stage. At this stage, the silk gland cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…For the sake of contrast tissue morphology, the target tissue silk glands and the non-targeted tissue of fat body were isolated on ice and fixed in 4% paraformaldehyde. Then the tissues were made of paraffin sections and were further stained by Hematoxylin and Eosin (HE) (Beyotime, Jiangsu, China) performed as described by Ji et al (2013) 19 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the sake of contrast tissue morphology, the target tissue silk glands and the non-targeted tissue of fat body were isolated on ice and fixed in 4% paraformaldehyde. Then the tissues were made of paraffin sections and were further stained by Hematoxylin and Eosin (HE) (Beyotime, Jiangsu, China) performed as described by Ji et al (2013) 19 .…”
Section: Methodsmentioning
confidence: 99%
“…The synthesized silk proteins in silk gland are more than 30% body weight of the organism. A silk gland synthesizes 6 × 10 9 fibroin proteins per second, which is more than 60 times faster than the rate of a human liver cell synthesizing serum albumin 19 20 . In this study, in order to improve delivery to an assumed target organ- SG, single amino acids, which are needed in large amounts during protein synthesis in SG of the silkworm, were linked to the QDs under investigation.…”
mentioning
confidence: 98%
“…In particular, BmATG1 , BmATG5 , BmATG6 , and BmATG8 were expressed in peritracheal athrocytes and gonads [31, 32]. A striking upregulation of various ATG genes during fifth larval instar and metamorphosis of this insect has also been observed in the larval midgut epithelium [32, 33], silk gland [29, 34, 35], and fat body [28, 32]. In fat body it has also been demonstrated that 20E levels affect the expression of these genes in vivo , confirming that the ecdysone titer in the hemolymph is linked to the induction of the autophagic program in the larval organs [28].…”
Section: A Glimpse Of the Past And A Look Into The Futurementioning
confidence: 99%
“…The economic importance of silkworms is dependent on the functionality of the silk gland (SG), a specialized organ that synthesizes silk proteins in the silkworm. The SG undergoes rapid development during the fifth instar larvae with the genomic DNA content in SG cells increasing 200–400000 times through the process of endomitosis [9, 10]. Consequently, the SG becomes the largest organ in silkworm abdominal cavity until the wandering stage.…”
Section: Introductionmentioning
confidence: 99%